Quasi-experimental evidence on the effectiveness of heart attack treatment in Germany - Corinna Hentschker; Ansgar Wübker (Applied Economics, 2020)
Medical technological progress has been shown to be the main driver of health care costs. A key policy question is whether new treatment options are worth the additional costs. In this analysis we assess the causal effect of percutaneous transluminal coronary angioplasty (PTCA), a major new heart attack treatment, on mortality. We use a full sample of administrative hospital data from Germany for the years 2005 to 2007. To account for non-random treatment assignment of PTCA, instrumental variable approaches are implemented that aim to randomize patients into getting PTCA independent of heart attack severity. Instruments include differential distances to PTCA hospitals and regional PTCA rates. Our results suggest a 4.5 absolute percentage point mortality reduction for patients who have access to PTCA compared to patients receiving only conservative treatment. We relate mortality reduction to the additional costs for this treatment and conclude that PTCA treatment is cost-effective in lowering mortality for AMI patients at reasonable cost-effectiveness thresholds.
Keywords: I11; I18; 610; Acute myocardial infarction; instrumental variables; mortality; quasi-experiment